Antimicrobial combination effects between curcuminoids and ampicillin against standard and clinical strains of staphylococcus aureus - Mohd Hassan, Norazian; Ibrahim, Sofiah; Md Taib, Nurhaya; Mohd Kamal, Laina Zarisa; Abdullah, Kahairi (2009)
Antimicrobials combination therapy has been used to treat infections for decades, with the goal of achieving synergistic effects, producing wider spectrums of coverage and minimizing any toxicity effects of conventional antimicrobial agents. Plant metabolites are among the suitable candidates to be used as antimicrobial and synergistic agents, which can help mankind to curb the evolution of drug-resistant strains of microbes. S. aureus infections are commonly treated with the penicillin group antibiotics such as ampicillin. However, S. aureus resistance to these antibiotics keeps on increasing and the therapy produce serious side effects, such as hypersensitivity or anaphylactoid reactions. Curcuminoids, which are responsible for the yellow colour of Curcuma longa L. or turmeric rhizomes possess bio-protective properties, which include promising antimicrobial activity with very low incidence of toxicity. For these reasons, our research effort turned to the antimicrobial combination study between ampicillin and curcuminoids in a view to enhance antimicrobial efficacy and developing safer drugs. In this study, the antimicrobial activity of curcuminoids mixture, which was fractionated from the dichloromethane extract of turmeric rhizomes was determined alone and in combination with ampicillin. The activity was tested against the standard strain of Staphylococcus aureus ATCC 25923 and the clinical isolate, which was obtained from patient diagnosed as having S. aureus infection at Hospital Tuanku Ampuan Afzan (HTAA), Kuantan. The minimum inhibitory concentration (MIC) for antimicrobial activity of the curcuminoids fraction and ampicillin, alone and in combination were evaluated by means of broth microdilution assay and chequerboard assay, respectively. The curcuminoid constituents of the fraction were analysed by TLC co-chromatography with authentic samples. TLC Agar Overlay Bioautographic assay was performed to screen the responsible curcuminoids for the antimicrobial activity of the fraction against both strains.The antimicrobial activity studies showed that the combination of ampicillin with curcuminoids fraction is likely to reduce the MIC of ampicillin compared with when tested alone against both strains of S. aureus. The results highlighted the occurrence of a pronounced synergism between 312.50 µg/ml of curcuminoids fraction and 1.56 µg/ml of ampicillin against the clinical strain with Fractional Inhibitory Concentration Index (FICI) of 0.25. These curcuminoids-drug combination augmented the antimicrobial activity of both ampicillin and curcuminoids fraction eight times compared with when tested alone. TLC profile of the curcuminoids fraction showed three yellow phenolic pigments, namely curcumin, demethoxycurcumin and bisdemethoxycurcumin, with the Rf values of 0.66, 0.46 and 0.31, respectively in dichloromethane(18):ethyl acetate(1) solvent system. TLC bioautographic assay has revealed these curcuminoids as the responsible compounds in the fraction that act synergistically with ampicillin. The finding suggests that curcumin, demethoxycurcumin and bisdemethoxycurcumin are promising synergistic agents for antimicrobial combination therapy with ampicillin. The synergistic combination is found useful in combating S. aureus resistance towards ampicillin and minimizing the undesired effects of the antibiotic.